Genome sequencing in plants and the genus Panax L. - Hiền, Lê Thị Thu; Boer, Hugo De; Manzanilla, Vincent; Huân, Hà Văn; Hải, Nông Văn (Vietnam Journal of Biotechnology, 2016)
Advances in genome sequencing technologies have created a new genomic era of life sciences research worldwide in which a number of modern and sophisticated techniques and tools have been developed and employed. Many countries have invested in plant genome sequencing as part of a sustainable development strategy. Each year, the number of plant genomes and transcriptomes sequenced has increased. The results obtained offer opportunities for fundamental and applied research, provide valuable data for identification of genes or molecular markers linked to traits that are important for selection, cultivation, and/or production. In Vietnam, partial or complete genome sequencing of crops has been recently conducted, primarily as part of international collaborative projects. The genus Panax L. (Araliaceae family) is comprised of several species of commercial value with narrow distributions such as P. bipinnatifidus Seem., P. stipuleanatus H.T.Tsai & K.M.Feng, and Panax vietnamensis Ha et Grushv. Despite their very important roles in traditional medicine, understanding of their genetic characteristics is still limited. Molecular studies on the genus have, so far, only evaluated limited markers for phylogenetic analysis. Therefore, genome sequencing of these important herbal plants is needed to understand their genetic characteristics, their evolutionary history and the genes and biochemical pathways contributing to medicinally important metabolites. This review summarizes all related genome sequencing technologies including the most recent advances in the last decade and their applications in genome and transcriptome sequencing of plants in general and in the genus Panax L. in particular.